Analisis Strategi Bersaing Dalam Persaingan Bisnis Properti Residensial (Rumah Tinggal) Di Kota Manado - Purba, Andi Sakti (JURNAL RISET BISNIS DAN MANAJEMEN, 2019)
The analysis shows that for now the attractiveness of the residential property industry in the city of Manado is still attractive or growing strong. But in the future based on the results of the analysis of the attractiveness of the property industry, it will experience a decline or saturation. The analysis of the industry characteristic matrix with indicators of incoming entrants to the present situation is in the attractive category. But going forward will decrease. While competition between companies in the industry for the present situation is attractive and in the future is in very attractive conditions with unstable conditions. Positioning carried out by PT. Wijaya Karya Realti is correct because if seen from the similarity of resources (resource similarity) compared to the closest competitor, CitraLand has a different position. In general, the concept of SCA can be applied as a marketing strategy of PT. Wijaya Karya Realti because of the overall indicators analyzed, the results are in the very strong category and the strong category. This indicates that the level of readiness of the requirements for applying the SCA concept is possibleKeywords: competitive advantage, Sustainable Competitive Advantage, Five Forces Porter